2019
DOI: 10.18332/tid/113093
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette use and its predictors: Results from an online cross-sectional survey in Poland

Abstract: INTRODUCTIONSince the invention of electronic cigarettes (ECs) in 2003, their use has spread worldwide; however, little is known about the profiles of EC users. Understanding the motivators for using ECs enables more accurate prediction of their use and more effective direction of pro-health activities. Our objective was to identify the factors that may influence the decision to use ECs and their possible adverse effects according to the experiences of EC users.METHODSA cross-sectional online survey was admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…More than four-fifths of participants believed that e-cigarettes could help quit smoking. Many studies found that e-cigarette users perceived e-cigarettes as being a healthier alternative to regular cigarettes, consistent with our study 9 , 25 . Although there were fewer toxic chemicals and of less concentration in e-cigarette aerosols than in traditional cigarettes, the unsubstantiated belief in the positive health effects of e-cigarettes might be harmful to the young population, especially the young never smokers 26 .…”
Section: Discussionsupporting
confidence: 92%
“…More than four-fifths of participants believed that e-cigarettes could help quit smoking. Many studies found that e-cigarette users perceived e-cigarettes as being a healthier alternative to regular cigarettes, consistent with our study 9 , 25 . Although there were fewer toxic chemicals and of less concentration in e-cigarette aerosols than in traditional cigarettes, the unsubstantiated belief in the positive health effects of e-cigarettes might be harmful to the young population, especially the young never smokers 26 .…”
Section: Discussionsupporting
confidence: 92%
“…The difference for us is that the prevalence of dry mouth is higher for e-cigarettes (33%) than for combustible tobacco (24%), which follows the findings of Peng et al 31 and Alhajj et al 19 . In previous reports, e-cigarettes were considered less harmful to users as an aid to smoking cessation and a replacement for regular cigarettes 28 , 34 , 35 . Pop et al 36 found that clinically healthy young tobacco smokers and e-cigarette users presented an increased number of micronuclei in the oral epithelial cells, compared to non-smoking individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Some data sources suggest that the prevalence of ENDS use in Poland was relatively high. A cross-sectional online survey conducted between 2016 and 2017 among Polish-speaking users of social networks reported 84.9% of ENDS ever users [16]. Finally, in a study by Jankowski et al conducted between 2017 and 2018 among university students in five student hostels in Poland almost half of the respondents (45%) declared ever use of ENDS [15].…”
Section: Introductionmentioning
confidence: 97%